2019
DOI: 10.1002/pri.1806
|View full text |Cite
|
Sign up to set email alerts
|

Home‐based isometric handgrip training on RBP in hypertensive adults—Partial preliminary findings from RCT

Abstract: ObjectiveThe aim of this study is to confirm whether 8 weeks of home‐based isometric handgrip (IHG) training would reduce resting blood pressure (RBP) in an adult Indian population.MethodologyHypertensive patients (Stage 1 [previously prehypertension] and Stage 2 [previously Stage 1 hypertension]) aged 30–45 years, male and female, were included. Intervention: Two groups were included (active control group and IHG training group at 30% of maximal voluntary isometric contraction). Outcomes of this study were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
12
0
5
Order By: Relevance
“…In three studies, isometric handgrip exercises [ 26 28 ] had similar target intensity (30% of maximal voluntary contraction). In one study, isometric wall squat training intensity was controlled by a target heart rate (HR) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, isometric handgrip exercises [ 26 28 ] had similar target intensity (30% of maximal voluntary contraction). In one study, isometric wall squat training intensity was controlled by a target heart rate (HR) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The HR should be compatible at the end of each stage from the isometric exercise test in visit 1 [ 28 ]. All home-based isometric exercise programs [ 25 , 26 , 28 ], except one handgrip study [ 27 ], showed reductions in blood pressure after interventions with a duration from 4 to 8 weeks (3 day/wk).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported reductions in resting blood pressure following isometric handgrip training in individuals without hypertension and hypertensive individuals with and without antihypertensive medication compared to a control (Badrov, Bartol, et al, 2013; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Farah et al, 2018; Herrod et al, 2019; Millar et al, 2008, 2013; Ogbutor et al, 2019; Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Souza et al, 2020; Taylor et al, 2003). However, other randomized controlled trials have observed no reduction in any resting blood pressure assessments after isometric handgrip training compared to a control group in medicated Stage 2 hypertensive adults (Pagonas et al, 2017; Stiller‐Moldovan et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Forty‐seven studies reported the chronic changes in resting blood pressure after isometric handgrip training (Ahmed et al, 2019; Allen et al, 2003; Alomari et al, 2010; Baddeley‐White et al, 2019; Badrov, Bartol, et al, 2013; Badrov, Horton, et al, 2013, 2016; Bank et al, 1998; Baross et al, 2017; Bentley et al, 2018; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Correia et al, 2020; Dempster et al, 2018; Dobrosielski et al, 2009; Farah et al, 2018; Gandhi, 2016; Garg et al, 2014; Goessler et al, 2018; Herrod et al, 2019; Hess et al, 2016; Howden et al, 2002; Lara et al, 2015; McGowan et al, 2006; McGowan, Levy, et al, 2007; McGowan, Visocchi, et al, 2007; Millar et al, 2007, 2008, 2013; Mortimer & McKune, 2011; Ogbutor et al, 2019; Okamoto et al, 2020; Pagonas et al, 2017; Peters et al, 2006, Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Saito et al, 2009; Sinoway et al, 1996; Somani et al, 2017, 2018; Somers et al, 1992; Souza et al, 2020; Stiller‐Moldovan et al, 2012; Taylor et al, 2003; Wiley et al, 1992; Yamagata & Sako, 2020; Zhang, 2003) (Table 2). In total, 22 studies included a nonexercise control group, three studies included a sham‐control group, one study provided a lifestyle modification program to both treatment and control groups, and 21 studies only had one or multiple isometric handgrip training groups.…”
Section: Methodsmentioning
confidence: 99%
“…Interessantemente, todos os 5 estudos conduzidos com mulheres idosas medicadas relataram redução da PA após o TRD (COELHO-JÚNIOR et al, 2018;DANTAS et al, 2016;MOTA et al, 2013;TERRA et al, 2008;TOMELERI et al, 2017) A presente revisão bibliográfica localizou 13 ensaios clínicos controlados e randomizados sobre o efeito do treinamento resistido isométrico em hipertensos (BADROV et al, 2013a;CAHU RODRIGUES et al, 2019;CARLSON et al, 2016;FARAH et al, 2018;GORDON et al, 2018;MILLAR et al, 2013;OKAMOTO;HASHIMOTO;KOBAYASHI, 2020;PAGONAS et al, 2017;PALMEIRA et al, 2021;PUNIA;KULANDAIVELAN, 2019;STILLER-MOLDOVAN;TAYLOR et al, 2003TAYLOR et al, , 2018. Doze estudos (92,3%) avaliaram homens e mulheres (BADROV et al, 2013a;CAHU RODRIGUES et al, 2019;CARLSON et al, 2016;FARAH et al, 2018;GORDON et al, 2018;MILLAR et al, 2013 et al, 2013a;CAHU RODRIGUES et al, 2019;CARLSON et al, 2016;FARAH et al, 2018;GORDON et al, 2018;MILLAR et al, 2013;PAGONAS et al, 2017;PALMEIRA et al, 2021;STILLER-MOLDOVAN;TAYLOR et al, 2003) avaliaram hipertensos em uso de medicação e 2 (15,4%) (OKAMOTO; HASHIMOTO; KOBAYASHI, 2020;…”
Section: Hipertensão Arterialunclassified